Development of Power Point-Based Learning Media Using Google Slides on Tharah Material for Class VII Students at MTs DDI Takkalasi - Khaerun Nisa; Muh. Dahlan Thalib; Buhaerah; Muhammad Saleh; Usman (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research was conducted with the aim of developing power point-based learning media using Google Slides on thaharah material. The learning media developed is used to make it easier for educators to deliver learning material in a more interesting way. This research was conducted by adopting the ADDIE development model which includes stages (Analyze, Design, Development, Implementation, Evaluation) including: (1) analysis, (2) product design, (3) development, (4) product implementation, (5) evaluation . Learning media was developed based on Power Point using Google Slides. The media that had been developed and passed expert and material validation tests were then tested on a limited basis with 5 people and on a large scale with 28 randomly selected class VII students at MTs DDI Takkalasi. The results of this research are in the form of power point-based learning media using Google Slides on thaharah material. The validity test was carried out twice, namely the media validity test with the results obtained an average of 3.2 which was categorized as very feasible in the appearance aspect and in the usage aspect, so an average of 2.6 was obtained which was categorized as feasible. At the material validation test stage, an average score of 3.33 was obtained, which was categorized as very feasible. Meanwhile, in the "content" aspect, an average score of 3.33 was obtained, which qualitatively falls into the very appropriate category. This shows that the "material" aspect of the PowerPoint-based learning media development product using Google Slides in the thaharah material is in accordance with the existing material content. The product practicality test showed that the average implementation results given by the two observers were 1.80:1.58 = 1.69 or (1.5 ? M ? 2.0) and the power point-based learning media using Google Slides on the thaharah material met the practical criteria for used in learning. The product effectiveness test was in the form of a learning outcomes test with results showing 0.52 which was included in the medium category 0.7 (N-gain) ? 0.3. From these results, it can be concluded that power point-based learning media products using Google Slides on thaharah material are effective for use in Islamic religious education learning. Then the results of observing student activity were 3.64 which is included in the category 3.5 ? Ps < 4.0, namely very active. Then the results of observing teacher activities showed that the average percentage of teacher activity from two meetings was 93.75%. This shows that learning using power point-based learning media products using Google Slides on thaharah material is going very well. And the results of the student response questionnaire showed an average result of 94.41%. Furthermore, regarding the criteria for student response questionnaires, it can be seen that the average of the analysis results is in the 81%-100% category with the criteria "very active".